DETERMINASI TINGKAT PENGANGGURAN TERBUKA (TPT) DI INDONESIA: ANALISIS DATA PANEL 34 PROVINSI TAHUN 2015-2024 - Febrian Khansada Zainghani; Ferry Hadiyanto (CV. Denasya Smart Publisher, 2026)
Unemployment remains one of the major labor market issues in Indonesia, particularly amid the demographic bonus that has increased the proportion of the working-age population. Without adequate job creation, this condition may intensify pressures in the labor market. This study aims to analyze the effects of regional government expenditure, investment, average years of schooling, provincial minimum wage, and the COVID-19 pandemic on the open unemployment rate in Indonesia. The study employs panel data from 34 provinces covering the period 2015–2024. Panel data regression analysis was conducted using the Common Effect Model, Fixed Effect Model, and Random Effect Model, with the best model selected through the Chow test and Hausman test. The results indicate that regional government expenditure with a two-year lag, average years of schooling, and the COVID-19 pandemic have a positive and significant effect on the open unemployment rate. Meanwhile, investment and the provincial minimum wage have a negative and significant effect on the open unemployment rate. These findings suggest that increased investment and appropriate wage policies can contribute to reducing unemployment, while the effectiveness of government expenditure and improvements in educational attainment need to be accompanied by expanded employment opportunities to prevent further increases in open unemployment.